El transhumanismo en los cuentos “El problema del amor” y “Volar como los pájaros” de Carlos Saldívar - Sanchez Roman, Fabiola Ingrid (2023)
This article explores the representation of transhumanism and its critical connotations in Carlos Saldívar’s short stories “El problema del amor” and “Volar como los pájaros”, within the framework of science fiction literature. The cen tral question driving this research is summarized as: ¿How are transhumanist concepts addressed and represented in Saldívar’s short stories, and in what ways are critical attitudes towards transhumanism reflected? The hypothesis holds that the representation in these stories reveals negative elements and ethical dilemmas, contributing to a critical view of transhumanism in Peruvian science fiction literature. The main objective is to perform a comprehensive analysis of the representation of transhumanist concepts in Saldívar’s short stories, unraveling elements that suggest adverse effects, ethical dilemmas and social criticism, thus contributing to a questioning perspective of transhumanism in Peruvian science fiction literature.